2021
DOI: 10.5194/nhess-21-2753-2021
|View full text |Cite
|
Sign up to set email alerts
|

Timely prediction potential of landslide early warning systems with multispectral remote sensing: a conceptual approach tested in the Sattelkar, Austria

Abstract: Abstract. While optical remote sensing has demonstrated its capabilities for landslide detection and monitoring, spatial and temporal demands for landslide early warning systems (LEWSs) had not been met until recently. We introduce a novel conceptual approach to structure and quantitatively assess lead time for LEWSs. We analysed “time to warning” as a sequence: (i) time to collect, (ii) time to process and (iii) time to evaluate relevant optical data. The difference between the time to warning and “forecastin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…As the debris consisted of boulders up to 10 m, continuous visual block tracking could be employed to estimate the displacement within the active area based on aerial orthophotos. Recent studies conducted with COSI-Corr confirmed this ongoing increase of mass wasting processes, with variable displacement rates ranging from 1-14 m in only 42 days [25].…”
Section: A Complex Landslidementioning
confidence: 91%
See 3 more Smart Citations
“…As the debris consisted of boulders up to 10 m, continuous visual block tracking could be employed to estimate the displacement within the active area based on aerial orthophotos. Recent studies conducted with COSI-Corr confirmed this ongoing increase of mass wasting processes, with variable displacement rates ranging from 1-14 m in only 42 days [25].…”
Section: A Complex Landslidementioning
confidence: 91%
“…Image registration, also known as image matching and image correlation, geometrically aligns images and allows tracking for accurate 2D change measurements in optical images. It has been used on a local to regional scale to assess motion fields for glaciological [8][9][10], earthquake [11][12][13], dune migration [14,15], rock glacier [16] and landslide studies [5,[17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…infrastructure damages (Guzzetti et al, 2020;Chikalamo et al, 2020;Hermle et al, 2021). The present work evaluates the design of a RILEWS using a mesoscale atmospheric model coupled to a logistic discriminator in the Southern Andes.…”
mentioning
confidence: 99%